ACUTE AND SUB-ACUTE ORAL TOXICITY EVALUATION OF METHANOL LEAF EXTRACT OF Vitellaria Paradoxa gaertn F. IN WISTAR RATS - Jimoh, AbdulFatai; Mohammed, Halima; Oloyede, Rukayyat Bukola; Yakubu, Musa Itopa; Mallam, Danjuma; Bashir, Asma'u I-J; Timothy, Micah; Sambo, Safiya Suleiman (FUDMA Journal of Sciences, 2026)
Toxicity studies of medicinal plants are essential for regulatory approval and for their therapeutic application Aim:The study aimed at evaluating the acute and sub-acute toxicity of the methanol leaf extract of Vitellaria paradoxa Gaertn F. in Wistar rats.Methods:Phytochemical screening of the extract was done using the methods of Trease and Evans (2004).The LD50 was determined using OECD (2008) Guideline 425, while the sub-acute toxicity test was conducted for 14 days at extract doses of 250, 500 and 1000 mg/kg (n=10) using OECD(2008)Guideline407.Carbohydrates,alkaloids,flavonoids,saponins,tannins, steroids/terpenes and cardiac glycosides were found in the extract but anthraquinones were absent.  No signs and symptoms of toxicity, and no mortality were recorded in the acute toxicity test and the LD50 of the extract was estimated to be greater than 5000 mg/kg. Sub-acute toxicity test of the extract produced significant increases (p
Keywords: Acute toxicity; Sub-acute toxicity; Vitellaria paradoxa methanol leaf extract